Macaque V1 representations in natural and reduced visual contexts: spatial and temporal properties and influence of saccadic eye movements - Ruiz, Octavio (American Physiological Society, 2012)
Vision in natural situations is different from the paradigms generally used to study vision in the laboratory. In natural vision, stimuli usually appear in a receptive field as the result of saccadic eye movements rather than suddenly flashing into view. The stimuli themselves are rich with meaningful and recognizable objects rather than simple abstract patterns. In this study we examined the sensitivity of neurons in macaque area V1 to saccades and to complex background contexts. Using a variety of visual conditions, we find that natural visual response patterns are unique. Compared with standard laboratory situations, in more natural vision V1 responses have longer latency, slower time course, delayed orientation selectivity, higher peak selectivity, and lower amplitude. Furthermore, the influences of saccades and background type (complex picture vs. uniform gray) interact to give a distinctive, and presumably more natural, response pattern. While in most of the experiments natural images were used as background, we find that similar synthetic unnatural background stimuli produce nearly identical responses (i.e., complexity matters more than “naturalness”). These findings have important implications for our understanding of vision in more natural situations. They suggest that with the saccades used to explore complex images, visual context (“surround effects”) would have a far greater effect on perception than in standard experiments with stimuli flashed on a uniform background. Perceptual thresholds for contrast and orientation should also be significantly different in more natural situations.